Trends of Hydroclimate Variables in the Upper Huai River Basin: Implications of Managing Water Resource for Climate Change Mitigation. (26th August 2020) - Girma, Abel; Yan, Denghua; Wang, Hao; Song, Xinshan; Qin, Tianlin; Dorjsuren, Batsuren; Gedefaw, Mohammed; Abiyu, Asaminew; Fikir, Dagim; Wang, Jianwei; Yadamjav, Otgonbayar
Abstract : The present study attempted to investigate the trends of mean annual temperature, precipitation, and streamflow changes to determine their relationships in the upper Huai river basin. The Mann–Kendall (MK), Sen's slope test estimator, and innovative trend detection ( ф ) (ITA) methods were used to detect the trends. According to the findings, average annual precipitation shows a descending trend ( ф  = −0.17) in most stations. An increasing trend was found only in Fuyang station ( ф  = 1.02). In all stations, the trends of mean annual temperature ( ф  = 0.36) were abruptly increased. During the past 57 years, the mean air temperature has considerably increased by 12°C/10a. The river streamflow showed a dramatic declining trend in all stations for the duration of the study period (1960–2016) ( ф  = −4.29). The climate variability in the study region affects the quantity of the streamflow. The river streamflow exhibits decreasing trends from 1965 onwards. The main possible reason for the declining stream flow in the study area is the declining amount of precipitation on some specific months due to the occurrence of climate change. The outcomes of this study could create awareness for the policymakers and members of the scientific community, informing them about the hydroclimatic evolutions across the study basin, and become an inordinate resource for advanced scientific research.